Enhanced expression and purification strategy for recombinant bacterially-expressed human hexokinase II - Ahmad Fuad, Fazia Adyani; Tanbin, Suriyea (Universitas Jenderal Soedirman, Purwokerto, Indonesia, 2021)
Dengue virus hijacks the host cellular mechanism to propagate and survive during viral infection, in which the central carbon mechanism plays a crucial role to upregulate DENV infection through the increase of human hexokinase II (HKII) activity. Since the enzyme governs the glycolytic pathway, it has potentials as a target for anti-dengue (DENV) drug development. In this study, the production of human hexokinase II protein has been enhanced by using bacterial system for anti-dengue therapeutic purpose. The HKII gene was cloned into pET28b vector and transformed into the E. coli strain BL21 (DE3) for HKII expression. In order to obtain soluble recombinant HKII in an active form, we optimized protein expression under specific conditions at 18°C for 19 hours using Terrific Broth media, in the presence of 0.5 mM isopropyl-2-D-thiogalactopyranoside (IPTG). The pET28b-HKII construct expressed in BL21(DE3) system exhibited adequate protein expression, thus, this construct was subsequently proceeded to purification process. The expressed protein was purified to homogeneity by a combination of Immobilized Metal Ion Affinity Chromatography (IMAC)and size exclusion chromatography (SEC), resulting in pure, active bacterially-expressed HKII with a specific activity of 56. 67U.mg-1. The amount of HKII obtained from 2 L culture is 80 mg, with a yield percentage of 10.5%. Hence in this study, human HKII has successfully been cloned and expressed as a soluble protein that can be utilized for further therapeutic studies.